2002
DOI: 10.1037/0002-9432.72.4.585
|View full text |Cite
|
Sign up to set email alerts
|

Errorless compliance training: Building a cooperative relationship between parents with brain injury and their oppositional children.

Abstract: Errorless compliance training, a noncoercive intervention for improving child compliance, was evaluated in a multiple baseline across-subjects design with 12 oppositional children (ages 2-7 years) and their brain-injured parents, who suffered from cognitive deficits, impulsivity, and/or emotional instability. Generalized and durable increases were observed in child compliance after treatment. Pre/post improvements were also noted on a measure of parent self-esteem. Errorless compliance training may be well sui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…This includes an impaired ability to maintain a warm and responsive relationship with their child, less nurturing, lower levels of active involvement with the children and less emphasis on obedience to rules and orderliness [9,[12][13][14]. Such difficulties were tragically illustrated by a high profile case in the Scottish system [15].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…This includes an impaired ability to maintain a warm and responsive relationship with their child, less nurturing, lower levels of active involvement with the children and less emphasis on obedience to rules and orderliness [9,[12][13][14]. Such difficulties were tragically illustrated by a high profile case in the Scottish system [15].…”
Section: Introductionmentioning
confidence: 98%
“…Those that may particularly alter parenting include cognitive problems such as reduced tolerance of noise [3,8] and being more irritable [9]. Reduced mobility can restrict everyday activities that facilitate parenting (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…For example, errorless learning strategies have been effectively employed with adults with cognitive and behavioral impairments secondary to BI [Ducharme et al, 2002;Ducharme, 2003]. Feeney et al [2001] found that behavioral supports can be used effectively in the community to assist individuals with significant behavior challenges after BI.…”
Section: Adjusting the Child's Environmentmentioning
confidence: 98%
“…Leith et al [2004] stated that environmental adjustment should include pro-moting a feeling of social belongingness for the child to the greatest extent possible. Specific adjustments recommended by these authors include increasing structure and predictability into the youth's routine, being proactive in behavioral approaches (i.e., using antecedent control whenever possible), involving people and activities that are meaningful to and desired by the youth, and using positive behavioral supports and strategies, such as errorless learning [Ducharme et al, 2002;Ducharme, 2003;Leith et al, 2004;Ylvisaker et al, 2005]. Braga et al [2005] conducted a RCT of an indirect, family-supported intervention for children with chronic impairments due to an earlier sustained BI.…”
Section: Adjusting the Child's Environmentmentioning
confidence: 99%
See 1 more Smart Citation